Hearing gain after myringoplasty in relation to the size of tympanic membrane perforation - Mondal, Sutanu Kumar; Biswas, Ashim Kumar; Huq, Md Mahmudul; Ali, Md Hasan; Md Kamruzzaman, -; Joarder, Md Abul Hasnat (Bangladesh Journal of Otorhinolaryngology, 2020)
Objectives: To assess hearing gain after successful myringoplasty in relation to the size of tympanic membrane perforation. Methods: This cross-sectional study was done in the department of otolaryngology and head neck surgery, BSMMU, Sahbag, Dhaka during the period of January 2009 to December 2010.A total of 60 patients were under went myringoplasty operation after taking detailed history, clinical examination and investigation. Preoperative and postoperative hearing assessment was done. Analysed data presented by various tables, graphics and figures. Results: In case of small size perforation preoperative mean bone conduction threshold was 7.66 dB, mean air conduction threshold was 34.14 dB and mean air bone gap was 26.48 dB. In case of medium size perforation preoperative mean bone conduction threshold was 9.61 dB, mean air conduction threshold was 44.48 dB. Mean air bone gap was 34.87 dB. In case of large size perforation preoperative mean bone conduction threshold was 13.12 dB, mean air conduction threshold was 59 dB, and mean air bone gap was 45.88 dB. Hearing loss increases with increasing size of perforation. Ahmed and Rahim (1979) showed in the study that hearing loss increases with increasing the size of the perforation which was relevant in the study. After myringoplasty post-operative mean air bone gap was 21.24 dB in small size, 21.74 dB in medium sized and 24 dB in large size. From the record improvement of mean air bone gap or hearing gain was 5.24 dB in small size perforation respectively. The different of air bone gap closure between small and medium size perforation was statistically significant by unpaired’ test. Conclusion: Hearing gain after myringoplasty is better in large size perforation. Bangladesh J Otorhinolaryngol; April 2019; 25(1): 54-59